Ink Formulation for Printed Organic Electronics: Investigating Effects of Aggregation on Structure and Rheology of Functional Inks Based on Conjugated Polymers in Mixed Solvents. Issue 2 (28th June 2020) - Schlisske, Stefan; Rosenauer, Christine; Rödlmeier, Tobias; Giringer, Kai; Michels, Jasper J.; Kremer, Kurt; Lemmer, Uli; Morsbach, Svenja; Daoulas, Kostas Ch.; Hernandez‐Sosa, Gerardo
Abstract: The utilization of solution‐processable organic semiconducting (OSC) polymers and the development of industrial‐relevant printing techniques enable cost‐efficient fabrication of optoelectronic devices for the mass market. Yet, the adaptation of viscoelastic properties of a functional ink to the respective printing technology is challenging. One crucial parameter is the formulation of the ink, which can be adjusted by selecting the combination of solvents that are mixed with the OSC. The current study considers model functional inks composed of a poly‐phenylene‐vinylene‐based OSC and two solvents, empirically known to be good. Their quality is quantified using the Hansen solubility parameters. The influence of the composition of the solvent mixture on structural, dynamical, and rheological behavior of the ink is investigated with light scattering, viscometry, and rheometry. Although both solvents are considered good, polymer aggregation is found at all compositions. Aggregation depends on composition in a nontrivial way. For dilute and semi‐dilute inks, the effects of aggregates on the ink viscosity are hidden by the difference in viscosities of the neat solvents. For elevated concentrations, the aggregates produce a hysteresis in the shear‐dependent viscosity, which should be considered when developing a functional ink for a particular printing technique. Abstract : The structural, dynamical, and rheological behavior of an organic semiconductor polymer ink is investigated. It is found that the aggregation of polymer chains is dependent on solvent composition. This effect has a significant influence on the fluid viscosity at printing‐relevant concentrations and should be considered when developing a functional ink.